2003
DOI: 10.1007/s00276-003-0164-4
|View full text |Cite
|
Sign up to set email alerts
|

Two rare anomalies of the left renal vein

Abstract: Two uncommon anatomical variations of the left renal vein were found on dissected specimens: a circumaortic venous ring and a retro-aortic bifid left renal vein. The first anomaly results from a persistence of the embryonic renal venous collar. The second one would be related to a particular pattern of left inferior vena cava. Both abnormalities have to be known for they may be undetected or be misleading in imaging. Other clinical implications are also considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 6 publications
0
18
1
3
Order By: Relevance
“…However, the bifid renal vein observed in our case was not one of the variants reported in this extensive study. In another case, Senecail et al [2] reported a retro-aortic bifid left renal vein; however, unlike our case, it was accompanied by a circumaortic venous ring. In another report, the left renal vein passed posterior to the aorta and gave off three branches, while the right renal vein was double [3].…”
Section: Discussioncontrasting
confidence: 60%
“…However, the bifid renal vein observed in our case was not one of the variants reported in this extensive study. In another case, Senecail et al [2] reported a retro-aortic bifid left renal vein; however, unlike our case, it was accompanied by a circumaortic venous ring. In another report, the left renal vein passed posterior to the aorta and gave off three branches, while the right renal vein was double [3].…”
Section: Discussioncontrasting
confidence: 60%
“…In most cases, these variations of duplication of the renal veins are clinically silent and remain unnoticed until they are discovered in the course of venography, operations or autopsy [18]. For kidney transplantation surgeons, the morphology of the renal vein takes on special significance, given that its variations influence the technical viability of the operation and may restrict mobilization of the vein [7,19]. Nonetheless.…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal imaging may be the source of technical difficulties in diagnostic or therapeutic angiography (Gillot) and may modify the values obtained by catheter sampling for suprarenal hormonal levels (Satyapal et al, 1999;Senecail et al).…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous anastomoses among these three pairs of vessels, the main of which is called renal anastomosis (or renal collar) (Senecail et al, 2003;Gillot).…”
Section: Discussionmentioning
confidence: 99%